Análisis jurisprudencial del Bitcóin - Chávez, Omar Ahomed (2021)
The general objective of the research is to analyze through comparative jurisprudence, the state’s position regarding the treatment and regulation of operations carried out using the digital currency of bitcoin; having as specific objectives to identify the public policy and the philosophical framework appropriate to this cryptographic currency.